2022
DOI: 10.3390/v14040759
|View full text |Cite
|
Sign up to set email alerts
|

Replicating Viral Vector-Based Vaccines for COVID-19: Potential Avenue in Vaccination Arena

Abstract: The “severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)” is the third member of human coronavirus (CoV) that is held accountable for the current “coronavirus disease 2019 (COVID-19)” pandemic. In the past two decades, the world has witnessed the emergence of two other similar CoVs, namely SARS-CoV in 2002 and MERS-CoV in 2013. The extent of spread of these earlier versions was relatively low in comparison to SARS-CoV-2. Despite having numerous reports inclined towards the zoonotic origin of the virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 99 publications
0
39
0
Order By: Relevance
“…Based on data review obtained during phase I, Phase II trials were conducted with larger cohorts as well as elderly age volunteers (18–85) with similar dose treatment of phase I. Also, the booster dose administration (prime-boost) was implemented when immunogenicity responses were inadequate ( Chavda et al, 2022 ).…”
Section: Viral Vector (Replicating) Vaccine Candidatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on data review obtained during phase I, Phase II trials were conducted with larger cohorts as well as elderly age volunteers (18–85) with similar dose treatment of phase I. Also, the booster dose administration (prime-boost) was implemented when immunogenicity responses were inadequate ( Chavda et al, 2022 ).…”
Section: Viral Vector (Replicating) Vaccine Candidatesmentioning
confidence: 99%
“…In the phase 2b/3 trial (NCT04990466), IIBR partnered with the US-based NRx Pharmaceuticals (Cromos, Brilife, Georgia) to complete late-stage clinical studies and mass immunization of the Georgian population in the year 2021. A randomized, multi-center, and observer-blind study was conducted on 550 volunteers in the age group of 18–90 with two intramuscular (IM) injections of the IIBR-100 (prime-boost) or an active comparator at days 0 and 28 days, and followed up was performed to 12 months post last vaccination ( Chavda et al, 2022 ). NRx announced that this vaccine not only does induce a single dose of a vaccine protecting the volunteers from SARS-CoV-2 challenge but also induces adequate levels of neutralizing antibodies against the Omicron.…”
Section: Viral Vector (Replicating) Vaccine Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the pathogen was unidentified, and the disease was contemplated as "pneumonia of unknown etiology." Soon afterward, a novel coronavirus (CoV) family was associated with the etiology of the illness (2). The four primary coronavirus subdivisions are alpha, beta, gamma, and delta.…”
Section: Introductionmentioning
confidence: 99%
“…A study of binding interactions, conducted by Lupala et al [19] using atomistic molecular dynamics simulations, revealed that binding of Omicron S-protein is stronger to the human ACE2 protein than the original strain. This might be attributed to changes at the ACE2-RBD junction that improved hydrophobic interactions and suppressed solvent-specific surface area [20,21]. Therefore, many of the approved monoclonal antibodies (mAbs) became ineffective or showed less activity against the Omicron variant.…”
mentioning
confidence: 99%